(untitled) (Research, Society and Development, 2022)
It is extremely important for managers of Brazilian public health institutions to use computational tools that allow the estimation of their costs in order to assist them in decision making. This importance becomes more relevant when it comes to Brazilian public health institutions, which need to keep monthly expenditures within the limited transfer of funds from the Unified Health System (SUS). Therefore, this study proposes the use of the ARIMA-RNA hybrid model as a technique and method for forecasting the total costs of hospitalizations in public institutions in the Brazilian Midwest, comparing it with the ARIMA and RNA_MLP models, treated separately, for the choice of the best. Data belonging to the databases on the website of the Department of Informatics of the SUS (DATASUS) were used, from 2017 to 2021, in a total of 60 observations. The Statistical Package for the Social Sciences (SPSS) software was used to run the ARIMA and RNA_MLP models. As a result, the superior performance of the ARIMA-RNA hybrid model was confirmed when compared to the ARIMA and RNA_MLP methods, treated individually, thus confirming its applicability to the objective, as it was the hybrid method that produced the lowest error, 2.20%, in detriment of the ARIMA and RNA_MLP models, with errors of 11.05% and 6.55%, respectively.